AMBIGUITAS TUBUH PEREMPUAN DALAM PRAKTIK SURROGATE MOTHER DALAM NOVEL A HOUSE FOR HAPPY MOTHER KARYA AMULYA MALLADI - Fadhliah, Dara Aghnia Nur; Adji, Muhamad; Hidayatullah, Mochammad Irfan (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2023)
The research was aimed at describing the ambiguity of women’s bodies involved in surrogate motherhood in the novel